Liquid membrane formulation for removal of kraft lignin from simulated liquid waste solution - Othman, Norasikin (Universiti Teknologi Malaysia, 2013)
Extraction of lignin from pulping wastewater as an external biofuel and in specialty chemicals will additionally benefit the chemical and automobile industries. Though lignin is nontoxic, it imparts brownish black colouration to the water bodies can cause environmental problems. Emulsion liquid membrane (ELM) technology is proposed to extract and recover the kraft lignin (KL) compound from the aqueous waste solution. This study investigated on development of a liquid membrane formulation for lignin removal from aqueous waste solution. Several parameters such as types and concentration of carrier, types of diluents and types of stripping agentswere studied. The results showed that the most favorable liquid membrane formulation is using Aliquat 336 as extractant, kerosene as diluents and sodium bicarbonate (NaHCO3) as stripping agent which is almost 93% of lignin was extracted.